The Legacy of the Friendship Route in the Development of Mexico City With an Inclusive, Empowering, and Equitable Perspective in Peace and Harmony - García Ayala, José Antonio; Gallegos Navarrete, Blanca Margarita (Journal of Leadership, Accountability and Ethics, 2023)
The Friendship Route, is a group of sculptures built for the 1968 Olympic Games, which was intended, according to Mathias Goeritz -who conceived it-, to humanize Mexico City through art. In conjunction with three other guest sculptures, these were created by sculptors selected as far as possible based on inclusion criteria for the diversity of geographic origins, religious beliefs, races and ideologies, but also genders. Helen Escobedo and Ángela Gurria were the only two women out of a total of 22 sculptors, and they played a leading role in opening and closing this sculptural path, thus leaving a legacy in qualitative terms on the basis of these configuration guidelines regarding the importance of the women in the way of developing the country's capital city. Thus, this sculptural route, Olympic heritage of all Mexicans, has been established since those days and until today, in a paradigmatic legacy at international level, with respect to the way in which cities can be territorialized emotionally and with meaning from the sculpture.